The vitamins : chemistry, physiology, pathology. - Sebrell, W. H. (William Henry), 1901-1992; Harris, Robert S. (Robert Samuel), 1904-1983 (Academic Press Inc., Publishers, 1954)
The Vitamins: Chemistry, Physiology, Pathology, Volume I emphasizes the chemical, physiological, and pathological aspects of vitamins. This volume contains four chapters. Each chapter discusses the vitamin's nomenclature, industrial preparation, biogenesis, occurrence in foods, effects of its deficiency, and metabolism. Other general topics covered in each chapter include the vitamin's specificity of action, toxicity, pharmacology, detoxification, requirements, and therapeutic activity. This volume evaluates vitamins such as vitamins A, carotenes, ascorbic acid, vitamin B12, and biotin. This b.